Ambulatory Thoracoscopic Pleurodesis Combined With Indwelling Pleural Catheter in Malignant Pleural Effusion - Foo, Chuan T.; Pulimood, Thomas; Knolle, Martin; Marciniak, Stefan J.; Herre, Jurgen (Frontiers in Surgery, 2021)
Background and objective: Malignant pleural effusion (MPE) often results in debilitating symptoms. Relief of dyspnoea and improvement in quality of life can be achieved with either talc pleurodesis or insertion of an indwelling tunnelled pleural catheter (IPC). The former requires a lengthy hospital stay and the latter is associated with lower pleurodesis rates. In response to limited hospital bed capacity, we developed a pragmatic approach in managing MPE by combining thoracoscopic talc poudrage and insertion of IPC into a single day case procedure. We present data on the safety and efficacy of this approach. Methods: Patients who had undergone the abovementioned procedure between 2017 and 2020 were analysed. Demographic data, hospital length of stay (LOS), histological diagnosis, rates of pleurodesis success and procedural related complications were collated. Patients were followed-up for 6 months. Results: Forty-five patients underwent the procedure. Mean age was 68.5  10.4 years and 56% were male. Histological diagnosis was achieved in all cases. 86.7% of patients were discharged on the day of the procedure. Median LOS was 0 (IQR 0-0) days. Successful pleurodesis was attained in 77.8% at 6-month follow-up. No procedure related deaths or IPC related infections were recorded. Conclusion: Ambulatory thoracoscopic poudrage and IPC insertion is a safe and effective option in the management of MPE. All patients received a definitive pleural intervention with 77.8% pleurodesis success at 6-months and majority of them discharged on the same day. Future randomised trials are required to confirm these findings.